Administrative Immigration Enforcement in Indonesia: A Case Study of Residence Permit Violations at the Palembang Immigration Office - Arief Febrianto; Gunawan Ari Nursanto; Rasona Sunara Akbar (Badan Strategi Kebijakan Hukum, 2025)
This study explores the enforcement of administrative immigration measures in response to residence permit violations committed by foreign nationals. Using a qualitative case study approach, it examines how such violations are managed by immigration authorities, focusing on enforcement patterns, operational challenges, and the effectiveness of administrative responses. Data were gathered through document analysis, field observations, and interviews with key personnel, supported by legal and policy reviews. The findings highlight a range of violations, including overstaying, misuse of residence permits, and lack of valid documentation. Administrative actions such as deportation, revocation of permits, and blacklisting were commonly applied. However, the enforcement process was found to be constrained by inconsistent interpretations of legal provisions, limited technological and human resources, and inadequate coordination among relevant institutions. Enforcement practices tended to be reactive, triggered by referrals or specific incidents, rather than part of a continuous monitoring system.Comparative legal and policy analyses across jurisdictions indicate that immigration enforcement regimes grounded in preventive, integrated, and rights-respecting frameworks tend to produce higher levels of voluntary compliance and systemic legitimacy. The study recommends key improvements, including clearer operational guidelines, the deployment of interoperable digital surveillance, inter-institutional coordination, and increased public engagement. By addressing these challenges, immigration authorities can enhance the consistency, efficiency, and accountability of their enforcement systems, contributing to improved migration governance and public order.